Promoting excess heat using chemical reactions – case study - Silva, Luís António Pinela da (2021)
Heat recovery and promotion is an invaluable asset on the road to decarbonization and organic reaction chemical heat pumps present sufficient arguments to become a successful solution if proper politico-economic support and incentives are established. This technology’s ability to recover low-temperature heat and promote it to usable temperatures allows savings regarding energy costs and significant decreases in greenhouse gas emissions. This work focused on the study and optimization of the isopropanol/acetone/hydrogen (IAH) and the tert-butanol/isobutene/water (tB/iB) systems regarding their performance and economic competitiveness (EComp). The main studies found that the IAH and the tB/iB systems reached performances of around 71% and 56%, respectively, however, their EComp left much to be desired. On this note, the IAH system underwent further experimentation focusing on i) the excess hydrogen in circulation, ii) the reactors’ operating pressures, and iii) the use of a distillation column as the system’s separation equipment. The first led to a decrease of 10% in the system’s performance, but its EComp improved around 20%. The second did not alter the system’s performance significantly, but resulted in an enhancement of its EComp by around 8%. The third resulted in an increase in the system’s heat capacity, since the column’s reboiler can be fed the same low-temperature heat as the endothermic reactor, which created a scenario for which the payback period can be determined. Unfortunately, the best value found was of 14 years, however, if implemented, this solution prevents the emission of approximately 7500 ton CO2/year. This work found that these systems are both technically and economically feasible, but suffer from poor economic performance. Despite this, their potential and relatively early stage of investigation should serve as motivation to improve upon this technology’s existing foundations, whether through the catalysts employed, reactive distillation solutions, or the development of entirely new systems.